Assessing feasibility in invasive plant management: a retrospective analysis of garlic mustard (Alliaria petiolata) control. (13th September 2016) - Corbin, Jeffrey D.; Wolford, Matthew; Zimmerman, Christopher L.; Quirion, Brendan
Abstract: Given the difficulty that habitat managers face in controlling invasive species, assessing a project's feasibility before implementation can be a useful exercise. We describe efforts to eradicate a population of garlic mustard ( Alliaria petiolata ) from an area of the Adirondack Park, United States. We applied a retrospective assessment of the feasibility of the project using 2 different decision support tools, the Invasive Plant Management Decision Analysis Tool (IPMDAT) and WeedSearch. We modeled several scenarios in each tool by varying parameters related to the effectiveness of control in order to test the sensitivity of project success to particular assumptions. Except for a small decline between 2007 and 2009, the population increased during the control period. The number of surveyed transects with at least one garlic mustard individual increased, as did plant density within transects. IPMDAT and WeedSearch analysis confirmed that eradication of the garlic mustard population at this site was unlikely. IPMDAT discouraged proceeding with the goal of eradication, and only recommended containment if control of seed production could be effective and subpopulations (e.g. transects) could be eliminated. WeedSearch estimated that time required to achieve eradication would range from 11 years if control was 100% effective to more than 50 years if control was only 90% effective. The application of tools such as IPMDAT or WeedSearch can aid project planning by giving invasive species managers a more realistic picture of the commitment that may be required in order to achieve specific restoration goals.